Bio Based Composites for Engineering Application and Sustainability Perspectives - Sari, Nasmi Herlina; Rivlan, Muhammad Nabil Fadhlurrohman (Journal of Fibers and Polymer Composites, 2025)
Type of the Paper: Editorial Corner